2021
DOI: 10.1080/14756366.2021.1874946
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous anhydrase activity of carbonic anhydrase II: cysteine is required for nitric oxide (NO) dependent phosphorylation of VASP in human platelets

Abstract: The carbonic anhydrase (CA) family does not only catalyse the reversible hydration of CO 2 to bicarbonate, but it also possesses esterase and phosphatase activity. Recently, bovine CA II and human CA II have been reported to convert inorganic nitrite (O¼N-O À ) to nitric oxide (NO) and nitrous anhydride (N 2 O 3 ). Given the ability of NO to mediate vasodilation and inhibit platelet aggregation, this CA II activity would represent a bioactivation of nitrite. There are contradictory reports in the literature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…CysSH, GSH and Cu 2+ are of particular importance in the Wilson’s disease; treatment with the synthetic thiol penicillamine (chelator) and exogenous Zn 2+ (substitution of Cu 2+ from its stores) have favorable effects on this disease (Farinati et al 2003 ). CysSH, GSH, Zn 2+ and Cu 2+ also play a key role in the nitrous anhydrase activity of carbonic anhydrase which is associated with formation of N 2 O 3 , GSNO, CysSNO and NO (Hanff et al 2016 , 2018 ; Zinke et al 2016 ; Tsikas 2021 ; Tsikas and Gambaryan 2021 ). Intra-platelet carbonic anhydrase seems to be of significance in the pharmacological nitrite-dependent inhibition of platelet aggregation via S -transnitrosylation reactions (Tsikas and Gambaryan 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CysSH, GSH and Cu 2+ are of particular importance in the Wilson’s disease; treatment with the synthetic thiol penicillamine (chelator) and exogenous Zn 2+ (substitution of Cu 2+ from its stores) have favorable effects on this disease (Farinati et al 2003 ). CysSH, GSH, Zn 2+ and Cu 2+ also play a key role in the nitrous anhydrase activity of carbonic anhydrase which is associated with formation of N 2 O 3 , GSNO, CysSNO and NO (Hanff et al 2016 , 2018 ; Zinke et al 2016 ; Tsikas 2021 ; Tsikas and Gambaryan 2021 ). Intra-platelet carbonic anhydrase seems to be of significance in the pharmacological nitrite-dependent inhibition of platelet aggregation via S -transnitrosylation reactions (Tsikas and Gambaryan 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…CysSH, GSH, Zn 2+ and Cu 2+ also play a key role in the nitrous anhydrase activity of carbonic anhydrase which is associated with formation of N 2 O 3 , GSNO, CysSNO and NO (Hanff et al 2016 , 2018 ; Zinke et al 2016 ; Tsikas 2021 ; Tsikas and Gambaryan 2021 ). Intra-platelet carbonic anhydrase seems to be of significance in the pharmacological nitrite-dependent inhibition of platelet aggregation via S -transnitrosylation reactions (Tsikas and Gambaryan 2021 ). Yet, involvement and importance of carbonic anhydrase and its PTM including S -transnitrosylation in the Wilson’s disease have been sparingly investigated thus far (Di Fiore et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…sGC is strongly activated in washed human platelets incubated with recombinant bovine CA2 together with nitrite [ 83 ], whereas others showed that human, bovine, or mouse CA2 does not regulate nitrite-dependent NO formation in blood [ 85 ]. Recently in experiments with washed human platelets, we showed that cysteine is required for nitrite-dependent sGC activation, which was independent from CA inhibitor [ 86 ], but this assumption needs future experimental confirmations. Certainly, different experimental conditions including washed platelets, whole blood, or animal/human experiments could lead to different and even controversial results, but this does not call into question that nitrate/nitrite/NO pathway plays a beneficial role in the cardiovascular system and in regulation of platelet reactivity.…”
Section: Nitrate/nitrite/no Pathwaymentioning
confidence: 99%
“…1 Recent reports on the CA enzyme showed its nitrous anhydrase activity in converting NO 2 − to NO and NO 2 ˙ via N 2 O 3 formation. 26 Besides CA-induced NO 2 − reduction, Warren and coworkers reported the reduction of Zn II -bound NO 2 − -incorporating thiol. 27 Kundu and coworkers recently reported the reduction of M–NO 2 − (M = Co or Zn) species to NO upon reaction with an ene-diol.…”
mentioning
confidence: 99%